Patching persistent pneumothorax in a neonate - Sumona Bose; Vishwas Rao; A. Nalina; Attibele Mahadevaiah Shubha (Hygeia Press di Corridori Marinella, 2023)
Introduction: Though autologous blood patch (ABP) pleurodesis is widely used in adults, its use in children is uncommon, with only one reported in a neonate thus far. Here, we report a late-preterm neonate with persistent air leak and concurrent Aspergillus infection, who was successfully treated with ABP, and we review the literature on pleurodesis.  Case report: A late-preterm baby girl born at 35 weeks of gestation was referred with respiratory distress since birth. She required intubation and high-frequency oscillatory ventilation (HFOV) as she did not respond to conventional ventilation. On day 2 of life (D2), she developed left pneumothorax and, on D3, right pneumothorax, requiring intercostal chest tube drains (ICDs). The child was extubated on D14, and the right ICD was removed on D18. However, the left pneumothorax persisted. Computerized tomography revealed right-sided consolidation and pneumatoceles, and persistent left pneumothorax. ABP was done on D23 and D25, with resolution of pneumothorax and removal of ICD on D27. Concurrently, pleural fluid cultures done on D16, D23 and D25 grew Aspergillus terreus, which was treated with voriconazole. The child is well at 3 months follow-up.  Conclusion: ABP for persistent pneumothorax is a safe, easy and inexpensive bedside procedure. Though its therapeutic role is well established in adults and older children, its use in neonates, especially in preemies, is less explored. The results are satisfactory, and it may be a feasible alternative to surgery when used in select neonates.